(untitled) (Research, Society and Development, 2023)
During the Emergency Remote Teaching, all in-person assessments were suspended, causing great discomfort and raising questions about the authenticity of the answers given in remotely administered exams without the presence of supervision to ensure that students did not copy answers from their peers (cheating). One of the options explored to minimize the risk of cheating was to develop quizzes with different numerical answers for each student, using the Calculated Questions feature provided in the Moodle virtual learning environment. How can we determine if this strategy was effective? To what extent can we trust that the requirement for a different numerical answer for each student will increase the likelihood that the correct answer was actually calculated by the respondent? In this article, 12 academic semesters (from 2016 to 2021) taught in Engineering courses were analyzed, using asynchronous weekly quizzes composed of Moodle Calculated Questions. By using the "time to respond" information, typical distribution curves were obtained, considering the first time the questions were presented. It was observed that, over time, the average response times and standard deviations decrease, indicating that students are obtaining the answers without applying the time that would be necessary for complex calculations required to obtain the answer. The objective of this study is to present a methodology capable of collecting indicators on the effectiveness of using "Calculated Questions" to prevent cheating, based on standard Moodle reports.